Energy Consumption of Water Running and Cycling at Four Exercise Intensities - Sabrina Demarie; Emanuele Chirico; Cecilia Bratta; Cristina Cortis (Sports, 2022)
Water exercise provides a workload in every direction of motion for training in a reduced impact environment. The selection of an appropriate physical activity and an individual exercise prescription are essential to obtain training effects. The aim of the present study was to determine individualised relative exercise intensities at four speeds of motion for water cycling and water running. Running was tested both in buoyancy and with the feet in contact with the bottom of the pool. To this purpose, gas exchanges, heart rate, and blood lactate were measured in each test session. Fourteen active, healthy females (23.2 ± 1.6 years) underwent a dry land maximal incremental protocol to exhaustion on a treadmill and hydrobike (HB); they engaged in water running with ground contact (RC) and water running suspended (RS) tests in a swimming pool at 30, 40, 50, and 60 cycles per minute (cpm), submerged at the individual xiphoid level. The four motion speeds of the three water exercise modalities ranged from 50% to 95% of the maximal heart rate and the maximal oxygen uptake, representing a moderate-to-vigorous training stimulus. RS elicited the lowest oxygen consumption, whereas HB demanded the significantly highest oxygen consumption and presented the highest blood lactate accumulation, with vigorous intensity being reached at 50 cpm and near maximal intensity at 60 cpm. It appears that water cycling could be more suitable for athletic training, whereas water running could be more appropriate for health and fitness purposes.